2006
DOI: 10.1089/ten.2006.12.1587
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Human Mesenchymal Stem Cells in 3D Fibrin Clots: Dependence on Fibrinogen Concentration and Clot Structure

Abstract: Natural biopolymers such as human fibrin are appealing to tissue engineers, because fibrin is biocompatible, bioresorbable, and essential in normal wound healing. There have been numerous studies to date to develop a fibrin-based injectable cell delivery system, albeit with varying success. We propose that the outcome of fibrin cell delivery can, in part, be attributed to the relative concentrations of fibrinogen and thrombin solutions (i.e., formulations) and the structure of the final 3D fibrin clot. Formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
167
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 36 publications
13
167
1
Order By: Relevance
“…Thrombin buffer solution, on the other hand, contains calcium and sodium chlorides. High fibrinogen, and to a lesser extent low thrombin, concentrations have been shown to reduce the proliferation of human MSCs [7][8][9] and dermal fibroblasts [3]. The fibrinogen concentration thresholds determined by these studies, however, varied from 18 to 50 mg/mL fibrinogen.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thrombin buffer solution, on the other hand, contains calcium and sodium chlorides. High fibrinogen, and to a lesser extent low thrombin, concentrations have been shown to reduce the proliferation of human MSCs [7][8][9] and dermal fibroblasts [3]. The fibrinogen concentration thresholds determined by these studies, however, varied from 18 to 50 mg/mL fibrinogen.…”
Section: Introductionmentioning
confidence: 83%
“…More recently, they also have been proposed as scaffolding for cell delivery in several tissue engineering applications [2]. Numerous in vitro studies, indeed, have demonstrated the ability of fibrin gels to support survival, proliferation, and/or differentiation of many cell types [3][4][5][6], including mesenchymal stromal cells (MSCs) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The fibrinogen/thrombin concentration in the FG preparation has been shown to affect the structural properties of the scaffold, and in turn influence the proliferation rate and morphology of hMSCs. 27 Therefore, alterations in FG scaffold microstructure can influence its function as a delivery scaffold for AAV2. The aim of the current study was to assess, in vitro, the structural characteristics of FG hydrogels containing varying fibrinogen concentrations, their AAV2-particles release kinetics, and subsequent transgene expression in target cells for articular cartilage tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…All of these advantages make FG an appealing scaffold for preclinical translational cartilage tissue engineering applications. It has been shown that diluted FG produces a more open fibrin network compared with undiluted FG scaffolds, 27 and that FG can act as an efficient scaffold for gene delivery. [28][29][30] In the current study, we investigated the effect of different fibrinogen dilutions during the preparation of FG scaffold on the delivery of AAV2 and their early effects on human BM-MSC (hBM-MSC) chondrogenesis in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercially available product, unlike that used in this study, is not suitable for tissue engineering applications as the high crosslinking density of the fibrin network prevents cell migration within the construct [39,40]. Moreover, the PRP gel used in our current study can be an autologous preparation, which can be obtained easily in large quantities, at no extra cost [26] .…”
Section: Page 18 Of 35mentioning
confidence: 99%